A handbook of statistical analyses using stata - Rabe-Hesketh, Sophia; Everitt, Brian (Chapman & Hall, 2000)
Succinctly describing a variety of statistical analyses that can be applied using Stata. This handbook describes the features of Stata - an exciting statistical package used for standard and non-standard methods of data analysis. A Handbook of Statistical Analyses Using Stata shows outlines this package\'s usefulness in: modeling complex data from longitudinal studies or surveys analyzing results from clinical trials or epidemiological studies enabling tailor-made analyses with its powerful programming language Each chapter identifies the appropriate analysis for a particular set of data. A brief account of statistical background is included in each chapter, but the primary focus is on using Stata and interpreting results. This handbook complements its two predecessors A Handbook of Statistical Analyses Using S-Plus and A Handbook of Statistical Analyses Using SAS.
Keywords: statistika jako téma; statistika, zdravotnická statistika; Statistics as Topic